Development of Arabic Language Teacher Performance valuation Models: A Literature Review on Relevant Indicators and Instruments in the Context of Higher Education - murdiono, murdiono (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2023)
This research aims to develop a performance evaluation model for Arabic language teachers in the context of higher education through a literature review of relevant indicators and instruments. The primary goal is to design a holistic evaluation approach that is in line with the needs of higher education in Arabic language instruction. The research method involves an in-depth analysis of literature covering indicators such as teaching ability, material comprehension, student engagement, and technology integration, as well as assessment instruments such as classroom observation, project assessment, and the use of information technology. The research findings highlight the importance of stakeholder integration, including Arabic language professors, students, and other relevant parties, in the development of the evaluation model. The results of the literature review provide a strong foundation for designing a model that can advance the quality of Arabic language teaching in higher education. The research conclusion emphasizes the urgency of improving the quality of Arabic language instruction and underscores the vital role of the evaluation model in achieving this goal. Therefore, this research makes a significant contribution by providing a theoretical basis for the development of a more effective evaluation model to enhance the quality of Arabic language education at the higher education level.